PEMBERDAYAAN MASYARAKAT MELALUI PELATIHAN PEMBUATAN MAKANAN LOKAL KRIPIK PISANG BAGI PELAKU USAHA MIKRO KECIL DAN MENENGAH - Bria, Lelianita Angriani; Fahik, Meksiani Nope Aliansa; Indriyati, Indriyati; Kaha, Hendrikus Likusina; Kleden, Marianus (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in rural areas face significant challenges in product innovation and quality consistency. This community empowerment program aimed to enhance the capacity of UMKM actors in Nekmese Village, South Amarasi District, Kupang Regency, through training in local food production, specifically developing chocolate and strawberry variants of banana chips. The method employed a participatory approach with experiential learning involving 34 UMKM actors (17 women and 17 men, aged 18-36 years). The training covered banana selection techniques, optimal frying temperature control (160-170°C), coating application methods, and sanitation standards. Data were collected through pre-test and post-test evaluations, direct observation, and interviews. Results showed significant improvements: knowledge scores increased by 93.5% (from 45.3 to 87.6), production capacity rose by 87.5% (from 8 kg to 15 kg per week), and product selling price increased by 67% (from IDR 15,000 to IDR 25,000 per 200g package). Quality consistency reached 90% compared to 45% previously, while weekly sales volume increased by 80% (from 25 to 45 packages). The program successfully achieved product diversification, enhanced technical skills, and improved economic impact for UMKM actors. Sustainable follow-up programs focusing on digital marketing training, cooperative formation, and continued technical assistance are recommended to maintain long-term development and competitive advantage in regional markets.